Analisis Nilai Moral dan Representasi Peran Gender dalam Cerita Rakyat Asal Usul Danau Lipan dari Kalimantan Timur - Bella Setyawati; Nurdin Nurdin (Lembaga Yasin AlSys, 2026)
Folklore plays an important role as a means of transmitting moral values as well as a medium that reflects social constructions, including the representation of gender roles in society. This study aims to describe the moral values and representation of gender roles in the folklore “Asal Usul Danau Lipan”. This study used a descriptive qualitative method with a content analysis approach. The research data were sourced from the story text in the book Kumpulan Cerita Rakyat Kutai by Anwar Soetoen et al. The data were collected through reading and note-taking techniques and then analyzed through the stages of data identification, classification, and description. The results showed that the folklore “Asal Usul Danau Lipan” contains moral values that encompass human relationships with oneself, fellow human beings, and God. In addition, the gender representation in the story shows male dominance, while women are portrayed as weak and dependent figures. Thus, this folklore not only contains moral values that are relevant to life but also reflects the gender constructions that develop in society. These findings imply the importance of a critical reading of folklore as material for literary studies, character education, and social reflection on gender relations.